(untitled) (Web of Teachers: Inderscience Research, 2025)
Preschool children constitute the most active and productive stage of human life. Games are light, enjoyable, and enthusiastic activities in the formation of their consciousness, thinking, perception, and mental activity, and are one of the main methods of the educational process. Because the main activity of a child in preschool age is play. Children develop primarily through play in adapting to the social environment, enriching their life experience, strengthening their character, understanding themselves, and actively communicating with the environment. It is precisely didactic games that are important for fully revealing the individual characteristics of each child, expanding the child’s worldview and adapting it to the external environment.